2020
DOI: 10.18231/j.ijohd.2020.043
|View full text |Cite
|
Sign up to set email alerts
|

Applications of robotics in orthodontics in COVID-19 pandemic

Abstract: Our intelligence is what makes us human, and robots are an extension of that quality. Robots play an important role in providing physical subordinates and even companionship in today's medical world. Orthodontics has always endeavored to improve the efficacy and efficiency of its appliances. The use of robots gives precise outcomes in less time and also reduces the risk of infection. This paper intends to collect literature from PUBMED, PUBMED central, Google Scholar and Sciencedirect on uses of robotics in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It has been reported that orthodontics robots may minimize the transmission risk of the SARS-CoV-2 virus from person to person, thereby protecting orthodontists and their patients during regular procedures [208] .…”
Section: Other Robotsmentioning
confidence: 99%
“…It has been reported that orthodontics robots may minimize the transmission risk of the SARS-CoV-2 virus from person to person, thereby protecting orthodontists and their patients during regular procedures [208] .…”
Section: Other Robotsmentioning
confidence: 99%